Differential Regulation of the Ribosomal Association of mRNA Transcripts in an Arabidopsis Mutant Defective in Jasmonate-Dependent Wound Response - Kimberlin, Athen; Holtsclaw, Rebekah E.; Koo, Abraham J. (Frontiers in Plant Science, 2021)
Jasmonoyl-L-isoleucine (JA-Ile) is a powerful oxylipin responsible for the genome-wide transcriptional re-programming in plants that results in major physiological shifts from growth to defense. The double T-DNA insertion Arabidopsis mutant, cyp94b1cyp94b3 (b1b3), defective in cytochrome p450s, CYP94B1 and CYP94B3, which are responsible for oxidizing JA-Ile, accumulates several fold higher levels of JA-Ile yet displays dampened JA-Ile-dependent wound responses – the opposite of what is expected. Transcriptomic and proteomic analyses showed that while the transcriptional response to wounding was largely unchanged in b1b3 compared to wild-type (WT), many proteins were found to be significantly reduced in the mutant which was verified by immunoblot analyses of marker proteins. To understand this protein phenotype and their hypothesized contribution to the b1b3 phenotypes, wounded rosette leaf samples from both WT and b1b3 were subject to a translating ribosome affinity purification RNA sequencing (TRAP-Seq) analysis. Over 1,600 genes whose transcripts do not change in abundance by wounding changed their association with the ribosomes after wounding in WT leaves. Consistent with previous observations, the total pool of mRNA transcripts was similar between WT and b1b3, however, the ribosome-associated pool of transcripts was changed significantly. Most notably, fewer transcripts were associated with the ribosome pool in b1b3 than in WT potentially explaining the reduction of many proteins in the mutant. Among those genes with fewer ribosome-associated transcripts in b1b3 were genes relating to stress response, specialized metabolism, protein metabolism, ribosomal subunits, and transcription factors, consistent with the biochemical phenotypes of the mutant. These results show previously unrecognized regulations at the translational level that are affected by mis-regulation of JA homeostasis during the wound response in plants.